Overview on laws in housing estate flood disaster: Historical perspectives on land use planning - Mohd Khalid, Al Hanisham (Serials Publications, 2017)
Developmental projects are mushrooming in Malaysia.This has contributed to the cases of flood disaster in Malaysia environment which affect various parties especially the communities. The recent flood disasters in Malaysia have caused substantial losses of lives and properties. Efforts have been taken to control this issue. These efforts include legal mechanism in the management of flood control to protect the rights of all victims.The aim of the government is to provide adequate quality and sustainable housing accommodation to citizens.It is evident that flood disasters have affected the well-being of residents in housing estates.Thus, it is necessary that flood disaster should be adequately controlled through concerted efforts including legal means.This paper intends to provide an overview on laws related to early stage of development housing estate; focusing on land and planning authority.Thus, this paper will discuss issues on land and planning authority as this is essential part in providing safety to the public against floods issues in an era of increased complexity and uncertainty.